A Mitochondria-Targeted Cryptocyanine-Based Photothermogenic Photosensitizer - Jung, Hyo Sung; Lee, Jae-Hong; Kim, Kyutae; Koo, Seyoung; Verwilst, Peter; Sessler, Jonathan L.; Kang, Chulhun; Kim, Jong Seung (Journal of the American Chemical Society, 2017)
Cryptocyanine-based probes exhibit highly efficient photothermal conversion and represent a new class of photothermal agents for use in photothermal therapy (PTT). With the thermal susceptibility of mitochondria in mind, we have prepared a mitochondria targeted, NIR-absorbing cryptocyanine probe (Mito-CCy) and evaluated its photophysical properties, photothermal conversion efficiency, biological compatibility, cytotoxicity, and mitochondrial localization in HeLa cells. Upon subjecting 0.5 mL of a PBS buffer solution (10 mM, pH 7.4, containing 50% DMSO) of Mito-CCy (0.5 mM) to 730 nm laser irradiation at 2.3 W/cm(2), the temperature of the solution increased by 13.5 degrees C within 5 min. In contrast, the corresponding cryptocyanine (CCy) lacking the triarylphosphonium group gave rise to only an similar to 3.4 degrees C increase in solution temperature under otherwise identical conditions. Mito-CCy also exhibited high cytotoxicity in HeLa cells when subject to photoirradiation. This light-induced cytotoxicity is, attributed to the endogenous production of reactive oxygen species (ROS) induced under conditions, of local heating. ROS are known to interfere with the mitochondrial defense system and to trigger apoptosis. By targeting the mitochondria, the present sensitizer-based photothermogenic approach is rendered more effective. As such, the system reported here represents the vanguard of what might be a new generation of organelle-targeted photothermal therapeutics.